O reassentamento dos refugiados colombianos e palestino no estado do Rio Grande do Norte - Cruz, Carlos André Lucena da (2008)
Since the second semester of 2004, the first refugees guided by ACNUR arrived at Potiguar s territory. Then we follow closely, with other local actors, the implementation and development of this innovative action, namely the resettlement of those refugees in Rio Grande do Norte. To accomplish this, we consider the concepts of territory, dispossession, repossession and international migration. The state of Rio Grande do Norte is a pioneer in the Northeast, in this type of action, since, before this experience, just Rio Grande do Sul and São Paulo were engaged in this kind of action. Therefore, this paper analyzes the process of resettlement of refugees, fulfilled in Rio Grande do Norte, between 2004 and 2005. The research broaches the regards that resulted in departure of these refugees from their respective territories (Colombia and Palestine) as well as the characteristics and prospects of the areas that hosted the refugees (Natal, Lajes e Poço Branco). Finally, the work deals with the results achieved afield, through interviews and photographic record, near by refugees